Effectiveness of Implementation of Tax Consultant Licensing Services Through the Application of the Tax Consultant Information System (Sikop) at the Center for Financial Profession Development Secretariat General of the Ministry of Finance - Tikno Suhendro; Agung Edi Rustanto; Yahya Rachmana Hidayat; Siti Mariam (Dinasti Research, 2024)
The aim of this research is to analyze the implementation of Tax Consultant Licensing Services through the Tax Consultant Information System Application (SIKOP) at the Financial Professional Development Center of the Secretariat General of the Ministry of Finance, by presenting a case study of the use of the SIKOP application. E-Government, whose aim is to provide the best service to the public in a transparent, effective and efficient manner, turns out that in its implementation it is still faced with various challenges which result in the ineffectiveness of e-government itself. The research uses qualitative methods by analyzing data through interviews, observation and documentation studies. This approach enables an in-depth understanding of the implementation of SIKOP and the e-Government challenges faced in the Ministry of Finance. The research results show a significant increase in the accessibility of licensing services and the acceleration of the licensing process since the adoption of SIKOP. However, the study also identified several shortcomings, including confusion regarding procedures, lack of personal interaction, and inadequate solutions. Therefore, improvements are needed in these aspects to ensure that tax consultant licensing services are in accordance with the desired public service principles. Managerial implications and suggestions for further research are also discussed to improve the quality and effectiveness of SIKOP as a tax consultant licensing service platform.